Determine the balance of the security level when the waiting period to be fixed in the General Company for Leather Industries - Sarmad Alwan Mohammed Saleh (Journal of Madenat Alelem University College, 2015)
The methods of statistical and scientific have become common use in solving administrative problems to reach the correct decisions in order to find optimal solutions to administrative problems facing the administration at different levels. The process of controlling inventories aimed at identifying the needs of the State Company For Leather Industries (SCLI) materials inventory and supplies the quality and quantity so as to ensure the achievement of these goals optimally This includes research pointing to some of the statistical tools and how to use them to control the level of the Safety Stock of the material processed from the local markets and so to avoid the two cases, the first non-accumulation of material in the stores as a capital investor and second to avoid a shortage situation that may affect the company depending on the actual demand that is variable and Lead time is fixed.